L’Évolution de la Bourse de Montréal depuis un demi-siècle - Lortie, Pierre (Assurances, 1982)
The author analyses the evolution of the Montreal Stock Exchange, as it was called in 1932, and has become Montreal Exchange. It has come a long way during this half of the century, narrated by Mr. Pierre Lortie, President. Here are some measures taken by successive administrations since the depression years: revision of controlling services, integration to Quebec economy, diversified field of options (shares, gold, contracts), opening on international markets. Mr. Lortie also points out the significative improvements and achievements of each Montreal Exchange presidential terms. So that the institution may become instrumental in the progress of our national economics and a very dynamic sector, not only in Quebec, but abroad.